2012
DOI: 10.1380/ejssnt.2012.297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mg<sub>2</sub>Si/MgO Nanofibers Using SiO<sub>2</sub> Nanofibers in Mg Vapor

Abstract: Mg2Si/MgO nanofibers were synthesized by the heat treatment of amorphous SiO2 nanofibers in Mg vapor, and their morphological and structural properties were then investigated. Well-aligned Mg2Si/MgO nanofibers with high density were synthesized, which preserves the general morphology of the original SiO2 nanofibers. The morphology and crystalline quality of Mg2Si/MgO nanofibers depend on the reaction temperature. This reaction provides a low cost method to synthesize nanoscale thermoelectric materials with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…16 The calculation results show that the mole ratio of MgO:Mg 2 Si is 2:1 as the SiO 2 completely converted into Mg 2 Si and MgO. 17 Figure 8 shows TEM images and the corresponding FFT patterns of the Mg 2 Si/MgO nanowire bundles synthesized at 450 ○ C and 630 ○ C. The results further confirm that the nanowires consist of Mg 2 Si and MgO.…”
Section: Syntheses Of Nanostructure Bundlesmentioning
confidence: 70%
See 2 more Smart Citations
“…16 The calculation results show that the mole ratio of MgO:Mg 2 Si is 2:1 as the SiO 2 completely converted into Mg 2 Si and MgO. 17 Figure 8 shows TEM images and the corresponding FFT patterns of the Mg 2 Si/MgO nanowire bundles synthesized at 450 ○ C and 630 ○ C. The results further confirm that the nanowires consist of Mg 2 Si and MgO.…”
Section: Syntheses Of Nanostructure Bundlesmentioning
confidence: 70%
“…It was reported that the Si phase is an intermediate product for the reduction of SiO x to Mg 2 Si and MgO using Mg vapor. 17 No peak due to the Si phase indicates that the reduced Si completely reacted with excess Mg vapor to form Mg 2 Si and the synthesized nanowires consist of Mg 2 Si and MgO. The \x" in SiO x is about 2, so the SiO x is assumed as SiO 2 .…”
Section: Syntheses Of Nanostructure Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though Mg 2 Si and MgO are randomly distributed, the bundle structure maintains as the SiO x nanofiber bundle [15,12]. As shown in Figure 1(d), it is observed that the highly oriented, well-aligned nanofibers grew in an orderly fashion with a high density on the substrates.…”
Section: Resultsmentioning
confidence: 91%
“…Mg 2 Si/MgO composite nanowire bundles were synthesized by the exposure of SiO x nanofiber bundles to Mg vapor. The detailed thermal treatment condition is described elsewhere [15].…”
Section: Methodsmentioning
confidence: 99%